(untitled) (Sains Humanika, 2017)
Most scholars have studied written discourse both in academic and professional setting within the scope of genre-based analysis, which demonstrate an increase interest in analysing the rhetorical structure of written texts. Conversely, there is a dearth of research in Malaysia that explains the rhetorical structure of argumentative essays from a genre analysis perspective. This paper introduces a genre-based corpus analysis using a compiled representative corpus of the argumentative essay for developing a rhetorical structure, also known as , an analytical framework to enhance the students’ writing skills. The compiled representative corpus was consisted of 24 argumentative essays. As a qualitative study, a corpus–based analysis is employed to explore the distinguished move patterns used in the argumentative essays. Using Hyland’s (1990) 11 move pattern as an analytical framework of the argumentative essay, this study revealed a list of moves and steps which were signaled by the linguistic features. Consequently, there were altogether 9 moves and 14 steps were identified in the three stages, namely Introduction, Argument and Conclusion. However, the moves used by the pre-university students in the study did vary from the model as new moves were marked in each stage. Pedagogically, the findings of this study were expected to guide in developing a framework for writing skills.